Learning the distribution of single-cell chromosome conformations in bacteria reveals emergent order across genomic scales - Joris J. B. Messelink (Nature Portfolio, 2021)
The order and variability of bacterial chromosome organization, contained within the distribution of chromosome conformations, are unclear. Here, the authors develop a fully data-driven maximum entropy approach to extract single-cell 3D chromosome conformations from Hi-C experiments on the model organism Caulobacter crescentus.